2018
DOI: 10.1111/jpn.12884
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary amylose/amylopectin ratio on serum and hepatic lipid content and its molecular mechanisms in growing‐finishing pigs

Abstract: This study was conducted to investigate the effects of dietary amylose/amylopectin ratio (DAR) on serum and hepatic lipid content, luminal short-chain fatty acid (SCFA) concentrations, and the expression of host genes involved in fat and glucose metabolism in liver and mucosa in growing-finishing pigs. Forty-eight Duroc × Landrace × Large White pigs (49.8 ± 2.8 kg) were randomly allocated to low amylose/amylopectin ratio (LR) and high amylose/amylopectin ratio (HR) groups, each group consisting of six replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
5
6
1
Order By: Relevance
“…We found that the mRNA level of FAS in piglets of the low AR (AR 0.31 and 0.14) groups were higher than those of the high AR groups. The present results, however, agree well with previous findings showing that ingestion of a low AR diet significantly elevated the lipogenic gene expression in growing-finishing pigs [31] and other animals [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…We found that the mRNA level of FAS in piglets of the low AR (AR 0.31 and 0.14) groups were higher than those of the high AR groups. The present results, however, agree well with previous findings showing that ingestion of a low AR diet significantly elevated the lipogenic gene expression in growing-finishing pigs [31] and other animals [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the slight increase (+ 5%) of the hepatic PC:PE-ratio in pigs of group IM10 was statistically significant, we postulate that this increase is not of biological relevance considering the marked elevation (+ 35%) of the hepatic PC:PE-ratio in severely steatotic obese Zucker rats compared with non-steatotic lean Zucker rats [16]. In line with our assumption, there was no indication of fatty liver induction as evident from the observation that hepatic TG concentrations of the pigs of all groups were within the physiological range reported from others [58,59]. With regard to individual phospholipid species, we observed that the percentages of PC and PE species with 6 double bonds were reduced in the liver of pigs of group IM10.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies indicated that dietary change widely affected endogenous enzymes activities (Yang, He, Yu, Yu, & Yin, 2018), while the current study showed that dietary different AM/AP ratio failed to influence α‐amylase, chymotrypsin, trypsin, lipase, sucrase and maltase activities. The reason might be caused by the weak secretory ability of young animals that broilers aged from 1 to 21 days were selected in this study.…”
Section: Discussioncontrasting
confidence: 46%